2001
DOI: 10.1016/s0896-6273(01)00343-9
|View full text |Cite
|
Sign up to set email alerts
|

Lack of the Burst Firing of Thalamocortical Relay Neurons and Resistance to Absence Seizures in Mice Lacking α1G T-Type Ca2+ Channels

Abstract: Huguenard and Prince, 1994a). The hyperpolarization of membrane potentials induced by the activation of GABA B receptors evokes rebound burst discharges in TC neurons (Crunelli and Leresche, 1991; McCormick and Bal, 1994). This characteristic firing pat-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
426
3
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 497 publications
(447 citation statements)
references
References 46 publications
16
426
3
2
Order By: Relevance
“…Definitive proof that thalamic LTS are mediated by T-type channels was provided by studies on transgenic mice, where knockout of the Ca v 3.1 gene abolished these spikes and burst firing (Fig. 2C) (206).…”
Section: A Low-threshold Calcium Spikesmentioning
confidence: 99%
“…Definitive proof that thalamic LTS are mediated by T-type channels was provided by studies on transgenic mice, where knockout of the Ca v 3.1 gene abolished these spikes and burst firing (Fig. 2C) (206).…”
Section: A Low-threshold Calcium Spikesmentioning
confidence: 99%
“…Specific ion channels mediate the rise in [Ca 2+ ] i within sperm, and many candidates for the principle Ca 2+ channel in sperm, including various voltagegated Ca 2+ channels, were proposed based primarily on studies using Ca 2+ imaging, immunolabeling, and patch-clamp experiments from sperm precursors [61][62][63]. However, genetic ablation studies suggested that these candidate proteins were not functionally necessary for male fertility or some compensatory mechanism for their loss may be present [64][65][66][67][68]. The molecular identity of the first sperm specific ion channel required for male fertility in mice was determined in 2001 with the cloning of CatSper1 [24].…”
Section: Calcium Channels and Hyperactivationmentioning
confidence: 99%
“…[72][73][74] As expected from this pharmacological observation, mice that lack ␣ 1G T-type Ca 2ϩ channels are resistant to absence seizures. 75,76 The three recessive mutations in Cacna1a (Ca v 2.1) that produce absence-like syndromes in tottering, leaner and rocker mice all impair channel function, reducing P/Q-type Ca 2ϩ currents. These and rolling Nagoya mice (with a further mutation on Cacna1a but not showing absence seizures) show ataxia and a wide variety of other central nervous system changes.…”
Section: Voltage-gated Calcium Channelsmentioning
confidence: 99%